Profil Pemahaman Konsep Matematika Siswa dalam Menyelesaikan Soal Persamaan Garis Lurus Ditinjau dari Self Efficacy - Wirdania, Wirdania; Pathuddin, Pathuddin; Lefrida, Rita; Alfisyahra, Alfisyahra (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to describe the understanding of mathematical concepts among 8th-grade students of SMP Negeri 15 Palu, specifically focusing on self-efficacy in the topic of linear equations. The type of research conducted is descriptive, utilizing a qualitative approach. The research method employed is the member-check method. The subjects selected for this study were 3 students from class VIII A of SMP Negeri 15 Palu, representing high, moderate, and low levels of self-efficacy as determined from the results of a self-efficacy questionnaire. They were subsequently administered a test on mathematical concept comprehension. The results of the research indicate that students with high self-efficacy demonstrate a very good understanding of mathematical concepts, mastering all concept comprehension indicators. Meanwhile, students with moderate self-efficacy master some indicators, and students with low self-efficacy only master the indicator of restating concepts. Thus, it can be concluded that subjects with high self-efficacy have a very good understanding of mathematical concepts, while subjects with moderate self-efficacy have a sufficiently good understanding, and those with low self-efficacy have a less adequate understanding of mathematical concepts. Keywords: Self Efficacy, Understanding of Mathematics Concepts